The Impact of Lactobacillus Infection During Pregnancy on Metabolic and Immune Parameters in Women 40 Days Post-Delivery: Dampak Infeksi Lactobacillus Selama Kehamilan terhadap Parameter Metabolik dan Imun pada Wanita 40 Hari Pasca Persalinan - Zahraa Ali Nashoor Alnawas; Kareema A. Dakhil (Academia Open, 2025)
Background: Lactobacillus normally plays a protective role in the maternal microbiome, yet under certain dysbiotic conditions it may be associated with metabolic and immunological disturbances during pregnancy. Specific Background: Evidence regarding postpartum health consequences of Lactobacillus infection remains limited, particularly its link to inflammatory and metabolic alterations. Gap: No studies have assessed metabolic and immune outcomes 40 days postpartum among women infected with Lactobacillus during pregnancy. Aim: This study examines postpartum metabolic profiles, inflammatory markers, and immune balance in women previously exposed to Lactobacillus infection. Methods: A cross-sectional comparison of 100 infected and 100 healthy women was conducted using clinical, biochemical, and immunological assessments. Results: Infected women exhibited higher fasting glucose, cholesterol, triglycerides, blood pressure, CRP, IL-6, IL-8, TNF-α, TPOAb, and TgAb, alongside lymphopenia and a Th1-dominant immune shift. Novelty: This study provides early evidence that Lactobacillus-associated dysbiosis in pregnancy may contribute to sustained metabolic and immune dysregulation beyond delivery. Implications: Findings highlight the importance of monitoring postpartum women with pregnancy-related dysbiosis and suggest a potential role of microbiome alteration in long-term maternal health. Highlights:• Distinct postpartum metabolic disturbances in infected women• Marked inflammatory activation associated with dysbiosis• Altered Th1/Th2 balance persisting after delivery Keywords: Lactobacillus Infection, Postpartum Metabolism, Immune Imbalance, Cytokines, Maternal Health